PENINGKATAN HASIL BELAJAR KIMIA MENGGUNAKAN MULTIMEDIA PADA MATERI IKATAN KIMIA KELAS X SMK NEGERI PARIGI SELATAN - Jumadil, Jumadil; Gonggo, Siang Tandi; Rahmawati, Sitti (Jurnal Akademika Kimia, 2013)
This study aims to determine whether to use the multimedia macromedia flash points can increase the activity and learning achievement of students in the chemical bond subject at class X SMK South Parigi. The sample is a class X SMK south Parigi is 46 students. This research is the Classroom Action Research (PTK) type which was implemented in three cycles, where each cycle consists of four stages, namely: planning, implementation, observation, reflection. Data obtained from each cycle were analyzed to determine the corrective action in the next cycle. Data collection is carried out through a test which consists of post tests at each end of the learning cycle 1, 2, 3 and also interviews for the entire series of events during the activity, as well as the observation sheet activities of teachers and students of each meeting. The collected data were statistically analyzed using the average of the class, classical absorption, and the thoroughness of learning. On the cycle I the average value of 6.87, the absorption of classical learning 68.81% and 68.42% completeness, in the second cycle the average value was 7.73, 77.32 and 88.37% and classical absorption the completeness study on a third cycle of the average value was 8.23, the absorption of classical learning 82.33% and 93.33% completeness. While on the student activity, the cycle I get an average score of 27 which is an increase in the second cycle to 36 and 40 in cycle III with both criteria. Therefore, the use of power point and multimedia macromedia flash in learning can improve student learning activities and results.